Insight into the Mechanisms and Clinical Relevance of Antifungal Heteroresistance - Yanyu Su; Yi Li; Qiaolian Yi; Yingchun Xu; Tianshu Sun; Yingxing Li (Journal of Fungi)
Antifungal resistance poses a critical global health threat, particularly in immuno-compromised patients. Beyond the traditional resistance mechanisms rooted in heritable and stable mutations, a distinct phenomenon known as heteroresistance has been identified, wherein a minority of resistant fungal cells coexist within a predominantly susceptible population. Heteroresistance may be induced by pharmacological factors or non-pharmacological agents. The reversible nature of it presents significant clinical challenges, as it can lead to undetected resistance during standard susceptibility testing. As heteroresistance allows fungal pathogens to survive antifungal treatment, this adaptive strategy often leads to treatment failure and recurring infection. Though extensively studied in bacteria, limited research has explored its occurrence in fungi. This review summarizes the current findings on antifungal heteroresistance mechanisms, highlighting the clinical implications of fungal heteroresistance and the pressing need for deeper mechanism insights. We aim to bring together the latest research advances in the field of antifungal heteroresistance, summarizing in detail its known characteristics, inducing factors, molecular mechanisms, and clinical significance, and describing the similarities and differences between heteroresistance, tolerance and persistence. Further research is needed to understand this phenomenon and develop more effective antifungal therapies to combat fungal infections.